Release oscillation in a hollow fiber – Part 2: The effect of its frequency on ions release and experimental verification - Lin, Ling; Li, Huigai; Liu, Yanping (Journal of low frequency noise, vibration, and active control, 2021)
The capillary oscillation in a hollow fiber greatly affects the process of ions release. Its approximate frequency is obtained, revealing a lower frequency predicts a longer release process, and the main factor affecting the frequency is studied theoretically and verified experimentally. The oscillation release can be also extended to drug release in tissue engineering.